Modulational instability in lossless left-handed metamaterials in nonlinear Schrodinger equation with non-integer dimensional space - Sylvere, Azakine Sindanne; David, Vroumsia; Justin, Mibaile; Joseph, Mora; Betchewe, Gambo; İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2023)
Apply style for article title, author, affiliation and email as per stylesheet. Several decades ago, antennas had simple shapes that were described in Euclidean geometry. Nowadays, scientists try to make the structure of fractal geometry for applications in the field of electromagnetism, which has led to the development of new innovative antenna devices. Non-integer dimensional space (NDS) is useful to describe the concept of fractional space in fractal structure for real phenomenon of electromagnetic wave propagation. In this work, we investigate effects of NDS and normalized frequency on modulational instability (MI) gain in lossless left-handed metamaterials (LHM). We derive the nonlinear Schrodindiger equation (NLSE) with non-integer transverse laplacian. By means of linear stability analysis method, MI gain expression is also determined. Different forms of figures are obtained due to the signs of group velocity dispersion (GVD) and defocusing/focusing nonlinearity. We show how the increasing value of the normalized frequency enhances the amplitude as well as the bandwidth of MI gain, and waves are more unstable due to non-integer dimension. The obtained results are new and have a relatively newer application in telecommunication by constructing the fractal-shaped antennas operating in multi-frequency bands.
Keywords: Modulational instability; left-handed metamaterials; nonlinear Schrodinger equation; non-integer dimensional space; linear stability analysis